2021
DOI: 10.1186/s12974-021-02145-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid inflammation and the blood-brain barrier in older surgical patients: the Role of Inflammation after Surgery for Elders (RISE) study

Abstract: Background Our understanding of the relationship between plasma and cerebrospinal fluid (CSF) remains limited, which poses an obstacle to the identification of blood-based markers of neuroinflammatory disorders. To better understand the relationship between peripheral and central nervous system (CNS) markers of inflammation before and after surgery, we aimed to examine whether surgery compromises the blood-brain barrier (BBB), evaluate postoperative changes in inflammatory markers, and assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Cytokine activation is only part of the neuroinflammatory process after surgery 1 . Other studies in this field have looked at the CSF to serum albumin ratio before and after surgery as a marker of BBB integrity, which was not investigated here 33 , 11 , 28 . A more detailed analysis of the CSF including cell count levels and the immunoglobulin subtypes IgM, IgG and IgA could be performed in future studies, as these would also have relevance in understanding the role neuroinflammation plays in PND 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine activation is only part of the neuroinflammatory process after surgery 1 . Other studies in this field have looked at the CSF to serum albumin ratio before and after surgery as a marker of BBB integrity, which was not investigated here 33 , 11 , 28 . A more detailed analysis of the CSF including cell count levels and the immunoglobulin subtypes IgM, IgG and IgA could be performed in future studies, as these would also have relevance in understanding the role neuroinflammation plays in PND 34 .…”
Section: Discussionmentioning
confidence: 99%
“… 32 One recent large-scale study found that in 29 patients undergoing either a total knee or total hip replacement, IL-6 levels were increased in plasma, but not in CSF, after an LP was performed at 1 month following the operation. 68 Levels of CRP were found to be increased in both CSF and plasma at 1 month. This may indicate that the cytokine-driven neuroinflammatory process had already resolved by 1 month after the operation.…”
Section: Post-operative Cytokine Levelsmentioning
confidence: 93%
“… Renner et al 2011 76 11 Hip arthroplasty Spinal Elective RCT with etoricoxib 0, 1.5, 2, 4, 8, 12, 24, 26, 32 and 48 hours after surgery IL-6, PGE2 Preoperative administration of etoricoxib lead to a reduction in serum IL-6 and pain levels, but no reduction was seen in CSF IL-6. Vasunilashorn et al 2021 68 29 Knee or hip total arthroplasty Spinal Elective Nil Before surgery and 1-month after surgery IL-6, CHI3L1, CRP In serum samples there was a significant increase in IL-6 at 1 month. Wang et al 2013 91 36 Aortic aneurysm surgery ± cardiopulmonary bypass Spinal Elective Nil Pre-incision, wound closure and every 4 hours for up to 5 days after surgery IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12p70, IFN-γ and TNF-α Plasma IL-6 levels were higher in the patient group which underwent cardiopulmonary bypass.…”
Section: Post-operative Cytokine Levelsmentioning
confidence: 96%
“…Cytokine activation is only part of the neuroin ammatory process after surgery [1]. Other studies in this eld have looked at the CSF to serum albumin ratio before and after surgery as a marker of BBB integrity [6,7,23]. We did not investigate markers of neuronal injury, such as S-100B, t-tau, neuronal speci c enolase (NSE) and neuro lament light chain protein (NFL), which other studies have investigated [24].…”
Section: Limitationsmentioning
confidence: 99%
“…Some cytokines tend to have a pro-in ammatory role; IL-1β, IL-6 and IL-8, while others, such as IL-4, IL-10 and IL-13, tend to be anti-in ammatory [4]. Studies on elective surgical patients have shown that there are greater post-operative cytokine increases in the cerebral spinal uid (CSF) than in plasma [5,6,7]. There is also some evidence to suggest that CSF cytokine changes may be associated with PND.…”
mentioning
confidence: 99%